Railway interlocking process - formal method for documenting railway junction interlocking and signalling processes. (2015) - Mocki, Jacek; Vlacic, Ljubo
A railway junction is a critical element for a reliable rail transport operation. An incorrectly selected interlocking type may cause delayed and unsafe rail transport operations. Our research shows that the use of railway junction interlocking and signalling formal methods enables a consistent comparison of various types of interlockings and interlocking technologies. Furthermore, it assists economic analyses of investment strategies into interlocking and signalling on railway junctions. This paper analyses the processes involved in signalling and compares different technologies. It presents a formal method developed for the purpose of comparing various technology implementations on a single, bidirectional railway junction. It describes currently implemented interlockings on railway junctions, discusses interlocking processes and proposes a consistent approach to building formal interlocking methods.